Special Editors' Introduction to the Special Issue on Award-Winning Papers from the IEEE Conference on Computer Vision and Pattern Recognition 2010 (CVPR 2010) - Darrell, Trevor; Hogg, David; Jacobs, David (IEEE transactions on pattern analysis and machine intelligence, 2012)
The nine award-winning papers in this special section were presented at the IEEE Conference on Computer Vision and Pattern Recognition (CVPR 2010)that was held 13-18 June 2010 in San Francisco, CA.